Evaluation of the effectiveness of auriculotherapy for insomnia - Luong, Thi Ngoc Yen; Le, Thi Thuy; Tran, Van Dung; Doan, Van Minh (Tạp chí Y Dược Huế, 2025)
Background: In modern life, Insomnia is a common problem that affects both health and living quality of people. Auriculotherapy, a traditional medicine – based approach is a therapeutic method in which specific points in auricles are stimulated to achieve specific therapeutic purposes. It is also a safe and simple procedure for treating insomnia. Objectives: To evaluate the effects of auriculotherapy on treating insomnia at Department of Traditional Medicine and Physical Therapy, Tan Phu District Hospital, Ho Chi Minh city. Methods: Includes 64 patients were treated with auriculotherapy, according to the research methodology, clinical trial, assess the results before and after treatment. Results: For Pittsburgh Sleep Quality Index (PSQI) total score, an average initial score 15.77 ± 1.88, decreased to 7.77 ± 2.48, the difference was statistically significant (p<0.05). The difference between low PSQI score and high PSQI score was associated with age (younger age) and disease duration (p<0.05). Conclusions: Auriculotherapy help improve sleep quality (sleep latency, sleep duration, sleep efficiency, sleep disturbance and PSQI score), the difference was statistically significant (p<0.05).